Warfarin and aspirin for primary prevention in patients with heart failure in sinus rhythm - Conti, Margherita; Trippoli, Sabrina; Messori, Andrea (Cardiovascular Diagnosis and Therapy, 2013)
Lala and co-workers (1) have argued that “while aspirin therapy decreases incident cardiovascular events, it also increases risk of major bleeding and hemorrhagic stroke”, and so “the benefit to risk ratio for aspirin use in primary prevention of cardiovascular events is less clear”. Heart failure (HF) in sinus rhythm is thought to be an indication for primary prevention not only with aspirin but also with warfarin, but this point has not been addressed in Lala’s article. Since aspirin and warfarin for patients with HF in sinus rhythm are an important therapeutic option particularly in the framework of individualized approaches, we have expanded the analysis of the evidence available in this area.